Terminal Tipe B Di Kabupaten Siak Dengan Penerapan Langgam Arsitektur Rumah Kajang - Tatang Erwansyah; Wahyu Hidayat; Mira Dharma S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Transport is essential element and function as liaison to the life and development of the economic, social, political, and mobility for population that is growing concurrently and follower the developments in various fields. Terminal is a ground transportation that serves to connect between regions, terminal is also a means for transportation of goods and people in area. The Terminal has an important role in economic development and regional development, because means of transportation facilities will trigger economic growth and regional development. In addition to the economy during this, the Malay culture in Indonesia has not yet been developed and widely exposed as other ethnic cultures. Terminal type B is planned and designed using Malay architecture theme. Reasons for the selection of Malay architectural theme as a backdrop of the location which in the region of Siak and to maintain the Malay culture in Siak district. The existence of a terminal type B with the application of architectural style House Kajang which is focused at building on the Siak Regency. Needs of the community infrastructure that will be capable of Siak liaise with social life, economic life and meet the needs of the Malay design centers which applicated on plan to the station, and make Siak district in meeting the needs of the growth mode of ground transportation.Keywords: Station, Station Type B, Kajang Malay Style.